Dietary phytochemicals as the potential protectors against carcinogenesis and their role in cancer chemoprevention - Liskova, Alena; Stefanicka, Patrik; Samec, Marek; Smejkal, Karel; Zubor, Pavol; Bielik, Tibor; Biskupska-Bodova, Kristina; Kwon, Taeg Kyu; Danko, Jan; Büsselberg, Dietrich; Adamek, Mariusz; Rodrigo, Luis; et al. (Clinical and experimental medicine, 2020)
Health-threatening consequences of carcinogen exposure are mediated via occurrence of electrophiles or reactive oxygen species. As a result, the accumulation of biomolecular damage leads to the cancer initiation, promotion or progression. Accordingly, there is an association between lifestyle factors including inappropriate diet or carcinogen formation during food processing, mainstream, second or third-hand tobacco smoke and other environmental or occupational carcinogens and malignant transformation. Nevertheless, increasing evidence supports the protective effects of naturally occurring phytochemicals against carcinogen exposure as well as carcinogenesis in general. Isolated phytochemicals or their mixtures present in the whole plant food demonstrate efficacy against malignancy induced by carcinogens widely spread in our environment. Phytochemicals also minimize the generation of carcinogenic substances during the processing of meat and meat products. Based on numerous data, selected phytochemicals or plant foods should be highly recommended to become a stable and regular part of the diet as the protectors against carcinogenesis.
Keywords: Anticarcinogenic Agents; Animals; fytonutrienty; Antioxidant; Dietary phytochemicals; Food; Chemoprevention; lidé; Metabolic activation; Carcinogens; Carcinogenesis; Detoxification; antikarcinogenní látky; karcinogeneze; Scavenging effect; karcinogeny; Phytochemicals; zvířata; potraviny; Humans